2015
DOI: 10.1109/tuffc.2014.006883
|View full text |Cite
|
Sign up to set email alerts
|

Dual-frequency acoustic droplet vaporization detection for medical imaging

Abstract: Liquid-filled perfluorocarbon droplets emit a unique acoustic signature when vaporized into to gas-filled microbubbles using ultrasound. Here, we conducted a pilot study in a tissue-mimicking flow phantom to explore the spatial aspects of droplet vaporization and investigate the effects of applied pressure and droplet concentration on image contrast and axial and lateral resolution. Control microbubble contrast agents were used for comparison. A confocal dual-frequency transducer was used to transmit at 8 MHz … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…For example, it is difficult to achieve efficient drug concentration in tumor sites because of their limited capacity for loading therapeutic agents, short circulation time, and large micrometer size. To address these problems, phase-change perfluorocarbon (PFC) nanodroplets have been developed 18 , 20 , 24 - 27 in which the liquid in the core of nanodroplets can vaporize to gas phase upon activation by ultrasound energy, called acoustic droplet vaporization (ADV) 28 - 30 . The stability of nanodroplets is increased, and they can accumulate in tumor tissues by passive targeting due to their nano-scaled size.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it is difficult to achieve efficient drug concentration in tumor sites because of their limited capacity for loading therapeutic agents, short circulation time, and large micrometer size. To address these problems, phase-change perfluorocarbon (PFC) nanodroplets have been developed 18 , 20 , 24 - 27 in which the liquid in the core of nanodroplets can vaporize to gas phase upon activation by ultrasound energy, called acoustic droplet vaporization (ADV) 28 - 30 . The stability of nanodroplets is increased, and they can accumulate in tumor tissues by passive targeting due to their nano-scaled size.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound is a form of the longitudinal mechanical wave that can be transmitted in the human body and is widely used in tumor imaging and therapy 30 - 35 . Different from the diagnostic ultrasound used in the clinic to force bubble elastic compression and expansion, more ultrasound energy is needed to induce conversion of nanodroplets into microbubbles and trigger local drug release 28 - 32 . However, it is difficult to induce droplet-to-bubble transition and destruction of hard-shelled (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Vaporization detection image has been demonstrated to be quite effective when transmitting at a high frequency (≥5 MHz) and receiving at a low frequency (≤1.5 MHz). 45,55 In this study, in order to achieve transcranial activation of PCCAs, VDI was implemented at different transmit frequencies ranging from 2.5 to 3.5 MHz to investigate whether VDI could provide higher contrast than UIAU. Besides increased penetration, low frequency transmit would potentially favor the vaporization and cavitation of low boiling point PCCAs and thus enhance therapeutic effects.…”
Section: Introductionmentioning
confidence: 99%
“…This technique, requiring the use of two mechanically scanned confocal piston transducers, has been adapted to develop an imaging system for capturing droplet vaporization events and generating high-sensitivity, high-contrast images. 24 The large difference between the activation pulse frequency and the listening frequency results in a weak response from microbubbles and tissue. In vitro results showed that ADV imaging was capable of generating a contrast-to-tissue ratio (>18 dB), as good as standard contrast agent imaging techniques.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro results showed that ADV imaging was capable of generating a contrast-to-tissue ratio (>18 dB), as good as standard contrast agent imaging techniques. 24 Imaging ADV at low frequency has several advantages. First, the penetration depth is increased because of the weak attenuation of low-frequency droplet content in tissue.…”
Section: Introductionmentioning
confidence: 99%